Perkembangan Pelaksanaan Pendidikan Agama Islam Di Madrasah Diniyah Al-Fitroh Sedayulawas Brondong Lamongan - Mujibur Rohman (Jurnal Pendidikan Islam, 2019)
Abstract: Early in its development and even into the early 70s, Madin was generally understood as a traditional religious education institution that grew and developed in rural communities through a unique social process. At that time, and even up to now, as well as an educational institution, Madin also acts as an influential social institution, its existence giving influence and color of religious life in the surrounding community; Not only in rural administrative areas, but not infrequently to cross the district where Madin was. The author will choose the location of research at Madrasah Diniyah Al-Fitroh Sedayulawas Brondong Lamongan The subject of research is Kyai, cottage management, ustadz, and santri. In the context of Islamic Religious Education, madrasah Diniyah Al-Fithroh is able to berkopentensi with other institutions, in addition supported by adequate facilities and infrastructure as well as lecturers who average graduates of higher education (Bachelor). In the process of teaching and learning, the santri are always nurtured and equipped with the ability to read the Qur'an properly and correctly in accordance with makhroj and tajwid correctly with curriculum and books in accordance with the Ministry of Religious Affairs and its own publications. Besides the learning activities to deepen Islamic scholarship also the students are given additional activities (Extras such as rikhlah ilmiayah, muhadloroh and tadabbur nature.